High-Resolution Imaging of Retinal Vasculitis by Flood Illumination Adaptive Optics Ophthalmoscopy: A Follow-up Study. (16th November 2020) - Errera, Marie-Hélène; Laguarrigue, Marthe; Rossant, Florence; Koch, Edouard; Chaumette, Céline; Fardeau, Christine; Westcott, Mark; Sahel, José-Alain; Bodaghi, Bahram; Benesty, Jonathan; Paques, Michel
ABSTRACT: Purpose : To monitor perivascular sheathing during the course of retinal vasculitis by flood illumination adaptive optics ophthalmoscopy (AOO). Methods : Perivenous sheathing and venous diameters were quantitatively analyzed by semi-automatic segmentation of AOO images in 12 eyes of treatment-naive patients with retinal vasculitis. Results : The width of venous sheathing ranged from 45 to 225 µm (mean 101.0 µm ± 54.3). In 10 cases, the underlying vein showed focal narrowing (mean ± SD 14% ± 10). Focal narrowing of arteries was also present in one eye. At presentation, width of sheathing and vessel diameters were not correlated with fluorescein leakage. During follow-up, 5 eyes showed an increase in vein diameter or resolution of narrowing and in 10 eyes a thinning of vascular sheathing was observed ( p = .003). Conclusions : Perivenous sheathing may be quantitatively analyzed and monitored by AOO. AOO may therefore contribute to monitor vascular sheathing during posterior uveitis.